Analysis of Temporal Changes in Growth and Gene Expression for Commensal Gut Microbes in Response to the Polyphenol Naringenin. (30th May 2018) - Firrman, Jenni; Liu, LinShu; Argoty, Gustavo Arango; Zhang, Liqing; Tomasula, Peggy; Wang, Minqian; Pontious, Sherri; Kobori, Masuko; Xiao, Weidong
In this study, the effect of the flavanone naringenin on the growth and genetic expression of the commensal gut microbes, Ruminococcus gauvreauii, Bifidobacterium catenulatum, and Enterococcus caccae, was analyzed. Analysis of growth curves revealed that Ruminococcus gauvreauii was unaffected by naringenin, Bifidobacterium catenulatum was slightly enhanced by naringenin, and Enterococcus caccae was severely inhibited by naringenin. Changes in genetic expression due to naringenin were determined using single-molecule RNA sequencing. Analysis revealed the following responses to naringenin: Ruminococcus gauvreauii upregulated genes involved in iron uptake; Bifidobacterium catenulatum upregulated genes involved in cellular metabolism, DNA repair and molecular transport, and downregulated genes involved in thymidine biosynthesis and metabolism; Enterococcus caccae upregulated pathways involved in transcription and protein transport and downregulated genes responsible for sugar transport and purine synthesis. For the first time, changes in growth and gene expression for commensal gut bacteria in response to naringenin were documented.